Fatal Hypogammaglobulinemia 3 Years after Rituximab in a Patient with Immune Thrombocytopenia: An Underlying Genetic Predisposition? - Jean-François Viallard; Marie Parrens; Frédéric Rieux-Laucat (Case Reports in Immunology)
We report the case of a young woman who developed, 3 years after stopping Rituximab (RTX) prescribed for immune thrombocytopenia (ITP), a severe immunodeficiency leading to fatal pulmonary Epstein–Barr virus-positive diffuse large B-cell lymphoma. Genetic analysis led us to identify four missense mutations known to affect immune-deficiency–associated genes (FAS-ligand (FASL) gene (p.G167R); perforin-1 (PRF1 (p.R55C) gene; the Bloom syndrome RecQ-Like helicase (BLM) gene and the Moesin (MSN) (p.A122T) gene). The heterozygous mutation in the FASL gene, not present in the Genome Aggregation Database or ClinVar database, could suggest atypical Autoimmune LymphoProliferative Syndrome and its role in this patient’s immunodepression is discussed. This observation strengthens the role of FASL gene mutation in severe clinical phenotypes of primary immune deficiency and raises new questions about the genetic background of ITP occurring in young people in a context of immunodeficiency.